2009
DOI: 10.1074/jbc.m807771200
|View full text |Cite
|
Sign up to set email alerts
|

The Glutathione System of Aspergillus nidulans Involves a Fungus-specific Glutathione S-Transferase

Abstract: The tripeptide glutathione is involved in cellular defense mechanisms for xenobiotics and reactive oxygen species. This study investigated glutathione-dependent mechanisms in the model organism Aspergillus nidulans. A recombinant dimeric protein of A. nidulans glutathione reductase (GR) contained FAD and reduced oxidized glutathione (GSSG) using NADPH as an electron donor. A deletion strain of the GR gene (glrA) accumulated less intracellular reduced glutathione (GSH), indicating that the fungal GR contributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 50 publications
5
80
0
Order By: Relevance
“…Thioredoxin reductase was assayed in a mixture comprising crude extract, 100 mM potassium phosphate (pH 7.5), 0.2 mM NADPH, 0.34 mM recombinant human insulin solubilized by the method of Holmgren et al (22) and 20 M recombinant thioredoxin (rTrxA) of Aspergillus nidulans (20,23). The reaction was started by adding rTrxA and the decrease in NADPH was measured at absorbance 340 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thioredoxin reductase was assayed in a mixture comprising crude extract, 100 mM potassium phosphate (pH 7.5), 0.2 mM NADPH, 0.34 mM recombinant human insulin solubilized by the method of Holmgren et al (22) and 20 M recombinant thioredoxin (rTrxA) of Aspergillus nidulans (20,23). The reaction was started by adding rTrxA and the decrease in NADPH was measured at absorbance 340 nm.…”
Section: Methodsmentioning
confidence: 99%
“…of PS at 30°C for 12 h, and total RNA was purified using the RNeasy plant mini kit (Qiagen, Venlo, The Netherlands) according to the manufacturer's instructions. First-strand cDNA was synthesized by incubating total RNA (10 g) in 10 l of reaction buffer comprising Oligo (dT) 20 (Toyobo, Osaka, Japan), 5 ϫ reverse transcriptase buffer and reverse transcriptase M-MLV (200 units) (Takara Bio, Kyoto, Japan) at 42°C for 90 min. Firststrand cDNA (330 ng) synthesized in the reaction was analyzed by quantitative PCR using iQ TM SYBR Green Supermix (BioRad) and MiniOpticon TM version 3.1 (Bio-Rad) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The explanation for the intriguing downregulation of gstB may be connected to the elevated glrA transcription. A study by Sato et al (2009) has shown that gstB is upregulated in a glrAD genetic background. In an hmbBD strain, the transcription of glrA is upregulated by 2.8-fold and gstB is downregulated by 2.9-fold, which would be consistent with downregulation of glrA upon gstA overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…the glutathione redox couple (Sato et al, 2009). The absence of glrA leads to the upregulation of the expression of trxR [thioredoxin reductase (TR), also known as trrA ], catB (CAT) and gstB which offsets the increased oxidative redox state due to GlrA depletion (Sato et al, 2009). The interplay between the glutathione couple system and other redox systems led us to the study of trxR and catB expression together with that of glrA.…”
Section: Effect Of Menadione and Diamide On The Redox State Of Hmbbd mentioning
confidence: 99%
See 1 more Smart Citation